2015
DOI: 10.1007/s00285-015-0899-7
|View full text |Cite
|
Sign up to set email alerts
|

Spaces of phylogenetic networks from generalized nearest-neighbor interchange operations

Abstract: Phylogenetic networks are a generalization of evolutionary or phylogenetic trees that are used to represent the evolution of species which have undergone reticulate evolution. In this paper we consider spaces of such networks defined by some novel local operations that we introduce for converting one phylogenetic network into another. These operations are modeled on the well-studied nearest-neighbor interchange (NNI) operations on phylogenetic trees, and lead to natural generalizations of the tree spaces that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…As such, a phylogenetic reconstruction method often uses nearest neighbor interchanges (NNIs) or other rearrangement operations to search for an optimal tree or network [8,9]. Recently, different variants of NNI have been proposed for RPNs [10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As such, a phylogenetic reconstruction method often uses nearest neighbor interchanges (NNIs) or other rearrangement operations to search for an optimal tree or network [8,9]. Recently, different variants of NNI have been proposed for RPNs [10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for unrooted phylogenetic networks, two operations have recently been developed that generalise the NNI operation from trees to networks (Huber et al, 2016a,b). While the first operation (Huber et al, 2016a) induces a metric on a relatively simple class of phylogenetic networks that do not have any overlapping cycles, the operation presented in (Huber et al, 2016b) draws its inspiration from the cubic graph literature and can be used to transform any unrooted phylogenetic network into any other such network.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they showed that the corresponding diameter of T C n is linear in n. NNI. The Nearest Neighbour Interchange (NNI) operation was defined on (unrooted) phylogenetic trees [20], but has recently been generalised to unrooted and rooted phylogenetic networks by Huber et al [13,14]. We define the NNI operation here only for tree-child networks, because we will only use it as a tool to count special sets of SNPR operations.…”
Section: Suboperationsmentioning
confidence: 99%